Cholesterol, high-density lipoprotein, and glucose index is associated with renal survival in patients with IgA nephropathy - Liu, Hong; Tang, Guijing; Yuan, Yuan; Gu, Peng; Wang, Anni; Zhao, Shuman; Jiang, Xue (Frontiers in Endocrinology, 2025)
BackgroundThe cholesterol, high-density lipoprotein, and glucose (CHG) index has emerged as a novel biomarker for insulin resistance (IR) and metabolic syndrome (MS). However, its prognostic role in IgA nephropathy (IgAN) remains underexplored. This study investigated the association between the CHG index and IgAN and aimed to clarify the importance of the CHG index in evaluating the prognosis of IgAN.MethodsThis single-centre retrospective study included 1791 patients with biopsy-confirmed IgAN who had more than 12 months of follow-up from October 2014 to September 2023. The optimal CHG index cut-off for renal endpoints was determined using receiver operating characteristic (ROC) analysis. Associations were assessed via correlation analysis, Cox regression, and Kaplan–Meier survival analysis.ResultsPatients were stratified into three baseline CHG index tertiles. High baseline CHG index was correlated with adverse clinicopathological features and reduced renal survival (Kaplan–Meier, log-rank=26.51; P<0.001). Correlation analyses revealed that the CHG index was positively associated with tubular atrophy/interstitial fibrosis, as well as intimal thickening and hyaline degeneration of renal arteries (P<0.001). The optimal CHG index cut-off for renal survival was 5.29 (sensitivity=63.1%, specificity=63.0%, AUC = 0.646), and patients were divided into a low group (CHG index ≤ 5.29; n=1,096) and a high group (CHG index >5.29; n=695). Subgroup analysis revealed that elevated CHG indices had a more pronounced prognostic value for renal outcomes in subgroups of patients with a BMI ≤ 24.9, a 24-hour urine protein level ≤ 3.5 g, an estimated glomerular filtration rate (eGFR)≤45 mL/min/1.73m², and an Oxford renal pathology classification (MEST-C)T0. Multivariate Cox regression analysis demonstrated that elevated CHG indices were significantly associated with worse renal outcomes in patients with IgAN (adjusted HR: 1.842; 95% CI: 1.044–3.249; P = 0.035).ConclusionElevated CHG index is an independent risk factor for predicting renal prognosis in IgAN. Compared with patients with low CHG indices, those with CHG indices > 5.29 have an 84.2% greater risk of poor renal outcomes.